Page 1 of 1

### Combining E=hv and c=ƛv

Posted: Sun Apr 15, 2018 11:45 pm
This past lecture Professor Lavelle showed an example where he combined E=hv and c=ƛv. This lead to the equation E=hc/ƛ. How did this combination result in this final equation?

### Re: Combining E=hv and c=ƛv  [ENDORSED]

Posted: Mon Apr 16, 2018 12:40 pm
Solve for v and plug v into E= hv.

### Re: Combining E=hv and c=ƛv

Posted: Mon Apr 16, 2018 2:06 pm
v = c/ƛ so E = hc/ƛ

### Re: Combining E=hv and c=ƛv

Posted: Wed Apr 18, 2018 8:07 pm
So we have E = hv, where h is Planck's constant and v is the frequency. We have c = ƛv where ƛ is the wavelength, c is the speed of light while v is also frequency. If we solve for v in c = ƛv we will get v = c/ƛ. Now we can plug that into E = hv where we will get E = hc/ƛ.

### Re: Combining E=hv and c=ƛv

Posted: Sun Apr 22, 2018 5:46 pm
from c=λv you solve for v and get v=c/λ. You substitute c/λ for v in the E=hv equation and get E=hc/λ

### Re: Combining E=hv and c=ƛv

Posted: Sun Apr 22, 2018 9:47 pm
First, you solve for v in the second equation, then plug that into E=hv.

### Re: Combining E=hv and c=ƛv

Posted: Sun Oct 14, 2018 7:08 pm
Will the value of c normally be given for use of the equation E=hc/ƛ?

### Re: Combining E=hv and c=ƛv

Posted: Sun Oct 14, 2018 7:47 pm
c is a constant, and it is likely that the value of it will be given to us in the equation sheet provided by Dr. Lavelle, but it might be useful to memorize it anyway.